2016
DOI: 10.20546/ijcrbp.2016.308.008
|View full text |Cite
|
Sign up to set email alerts
|

The Phytochemical Constituents of Vossia cuspidata and Synedrella nodiflora

Abstract: An investigation into the bioactive compounds in Synedrella nodiflora (leaf) and Vossia cuspidata (stem) was carried out. Soxhlet extraction, aqueous extraction and wet extraction methods were carried out using chloroform and water as the solvents. The extract obtained for Vossia cuspidata stems was 14.0%, 12.6% and 7.85% while that of Synedrella nodiflora leaves were 11.85%, 9.05% and 5.30% respectively. Phytochemical analysis of Vossia cuspidata stem showed the presence of carbohydrates, glycosides, terpenoi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 2 publications
0
7
0
Order By: Relevance
“…It reproduces only by rhizomes and spreads horizontally on the water's surface or along the riverbanks (Shehata, 1996). V. cuspidata can resist drought, high pH, loamy soil, and waterlogged areas [20]. It reaches a height of 3 m above the water surface.…”
Section: Introductionmentioning
confidence: 99%
“…It reproduces only by rhizomes and spreads horizontally on the water's surface or along the riverbanks (Shehata, 1996). V. cuspidata can resist drought, high pH, loamy soil, and waterlogged areas [20]. It reaches a height of 3 m above the water surface.…”
Section: Introductionmentioning
confidence: 99%
“…(hippo grass) of the family Poaceae is an aquatic perennial grass, which grows laterally as well as vertically up to 3 m height. According to Raphael et al (2016), the hippo grass is mainly found in the rainforest regions of the world including tropical Africa and Southeast Asia. It grows rooted along rivers with slow water flow and on the edges of lakes and streams (IUCN 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Vossia cuspidata (Hippo grass in English) is a perennial emergent macrophyte of the Poaceae family [28]. Although the plant is rarely studied in its distribution areas, it is a promising forage and medicinal plant that has many important constituents such as proteins, carbohydrates, glucosides, alkaloids, terpenoids, and flavonoids, in addition to a valuable essential oil [29][30][31][32][33]. The biosynthesis of CuO/ Ag/ Au monometallic and CuO-Ag-Au trimetallic nanoparticles using the extracted PS of V. cuspidata leaves was not yet reported.…”
Section: Introductionmentioning
confidence: 99%